Surface triggered stabilization of metastable charge-ordered phase in SrTiO3 - Eom, Kitae; Chung, Bongwook; Oh, Sehoon; Zhou, Hua; Seo, Jinsol; Oh, Sang Ho; Jang, Jinhyuk; Choi, Si Young; Choi, Minsu; Seo, Ilwan; Lee, Yun Sang; Kim, Youngmin; et al. (Nature Communications, 2024)
Charge ordering (CO), characterized by a periodic modulation of electron density and lattice distortion, has been a fundamental topic in condensed matter physics, serving as a potential platform for inducing novel functional properties. The charge-ordered phase is known to occur in a doped system with high d-electron occupancy, rather than low occupancy. Here, we report the realization of the charge-ordered phase in electron-doped (100) SrTiO3 epitaxial thin films that have the lowest d-electron occupancy i.e., d1-d0. Theoretical calculation predicts the presence of a metastable CO state in the bulk state of electron-doped SrTiO3. Atomic scale analysis reveals that (100) surface distortion favors electron-lattice coupling for the charge-ordered state, and triggering the stabilization of the CO phase from a correlated metal state. This stabilization extends up to six unit cells from the top surface to the interior. Our approach offers an insight into the means of stabilizing a new phase of matter, extending CO phase to the lowest electron occupancy and encompassing a wide range of 3d transition metal oxides.